A = b is given to us
Multiply both sides by c to get
a = b
a*c = b*c
The rule to multiply both sides by c is the multiplicative property of equality
Then on the right side, replace c with d. This replacement is possible due to the fact that c = d. This is using the substitution property.
So we go from
a*c = b*c
to this
a*c = b*d
Answer:
Step-by-step explanation:
if the faster hose is ten minutes faster and both together only takes 12 minutes then the secound one by it self should take 22 mins. i think im not sure tho